Hypolipidemic effect and molecular mechanism of ginsenosides: a review based on oxidative stress - Jin, Wei; Li, Chunrun; Yang, Shihui; Song, Shiyi; Hou, Weiwei; Song, Yang; Du, Quanyu (Frontiers in Pharmacology, 2023)
Hyperlipidemia is considered a risk factor for cardiovascular and endocrine diseases. However, effective approaches for treating this common metabolic disorder remain limited. Ginseng has traditionally been used as a natural medicine for invigorating energy or “Qi” and has been demonstrated to possess antioxidative, anti-apoptotic, and anti-inflammatory properties. A large number of studies have shown that ginsenosides, the main active ingredient of ginseng, have lipid-lowering effects. However, there remains a lack of systematic reviews detailing the molecular mechanisms by which ginsenosides reduce blood lipid levels, especially in relation to oxidative stress. For this article, research studies detailing the molecular mechanisms through which ginsenosides regulate oxidative stress and lower blood lipids in the treatment of hyperlipidemia and its related diseases (diabetes, nonalcoholic fatty liver disease, and atherosclerosis) were comprehensively reviewed. The relevant papers were search on seven literature databases. According to the studies reviewed, ginsenosides Rb1, Rb2, Rb3, Re, Rg1, Rg3, Rh2, Rh4, and F2 inhibit oxidative stress by increasing the activity of antioxidant enzymes, promoting fatty acid β-oxidation and autophagy, and regulating the intestinal flora to alleviate high blood pressure and improve the body’s lipid status. These effects are related to the regulation of various signaling pathways, such as those of PPARα, Nrf2, MAPK, SIRT3/FOXO3/SOD, and AMPK/SIRT1. These findings suggest that ginseng is a natural medicine with lipid-lowering effects.